Genotype Assessment of Chilli (Capsicum annuum L.) for Sustainable Production in Southern Odisha - Goddu, Sai Manoj; Mishra, Archana; Jena, Chinmaya; Prusty, Ajay Kumar (NG Agricultural Sciences, 2025)
This study aimed to evaluate the performance of 13 genotypes of chilli (Capsicum annuum L.) under the agroclimatic conditions of Southern Odisha during the Rabi season of 2022-23. The experiment was conducted at the PG Instructional Research Farm, Bagusala, using a Randomized Block Design with three replications. The results revealed significant variations among the genotypes in terms of growth, flowering, and yield parameters. The genotype Arka Abhir consistently demonstrated superior performance, achieving the highest plant height, number of primary branches, leaf area, fruit length, fruit girth, average fruit weight, and overall fruit yield. These findings suggest that Arka Abhir is well-suited for cultivation in Southern Odisha due to its adaptability to local conditions and high yield potential. The genotype Andhra Local also showed promising results, particularly in fruit yield. The study highlights the importance of selecting appropriate genotypes and adopting scientific cultivation practices to enhance productivity and ensure sustainable chilli production. Future research should focus on exploring the potential of other genotypes, improving cultivation techniques, and addressing challenges related to climate change and pest management.